Arundel House (To The South). (From An Etching By Hollar.) Arundel House (To The North). (From An Etching By Hollar.) (Tufts Archival Research Center, 2005)
This illustration is from Walter Thornbury "Old and new London, a narrative of its history, its people, and its places, vol. 3"